Requirement of extracellular complement and immunoglobulin for intracellular killing of micro-organisms by human monocytes. - Leijh, P C (1979)
The role of serum factors in the intracellular killing of bacteria by monocytes was studied on the basis of an assay independent of phagocytosis. After 3 min of phagocytosis of preopsonized bacteria and removal of noningested bacteria, the monocytes containing bacteria are reincubated for various periods and the number of unkilled bacteria is determined by a microbiological method after lysis of the cells. Evidence that this assay measures the killing of ingested bacteria was provided by scanning electron microscopy, lysostaphin treatment, and the effect on the rate of intracellular killing of inactivated serum lacking specific opsonic activity. Intracellular killing of Staphylococcus aureaus, S. epidermidis, and Escherichia coli by human monocytes does not occur or is low in the absence of serum, and maximal killing is only reached when fresh serum is present; intermediate values are obtained in the presence of heat-inactivated serum. These findings indicate that complement stimulates intracellular killing. Isolated heterogeneous immunoglobulin (Ig)G, pFc fragments of heterogeneous IgG, and both IgG1 and IgG3 stimulate intracellular killing of S. aureaus by monocytes to the same degree as heat-inactivated serum. Sphingomyelinase, which decreases the number of Fc receptors, and neuraminidase, which increases these receptors, respectively, decreased and increased the intracellular killing, whereas anti-monocyte serum completely abolished the stimulation of intracellular killing by inactivated serum. These results prove that interaction of the Fc receptor with the Fc part of IgG is required for the intracellular killing. Inhibition of the activation of complement components via the alternative pathway gave a considerable reduction in the intracellular killing of S. aureaus; impairment of the activation via the classical pathway had no effect. The addition of complement components to heat-inactivated serum showed that intracellular killing is maximal only when C3b is generated. Reduction of the number of C3b receptors in the membrane by trypsin or pronase decreased intracellular killing in the presence of fresh serum; anti-monocyte serum completely abolished the stimulation of intracellular killing by fresh serum. These results lead to the conclusion that intracellular killing is also dependent on the interaction between C3b and its receptor in the membrane.